Gender Integration in Eastern African Farmers Federation Strategies: Position Paper - Bamanyaki, Patricia A; Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The successful integration of a gender and youth perspective in an organisation's work requires an explicit recognition in its overarchning documents. Based on a desk review and analysis of two EAFF strategies through a gender lens, the paper examines the aim and extent of gender and youth integration in EAFF and proposes recommendations to strengthen gender and youth integration in strategies and programmes to enhance the achievement of the organisational goal for the Eastern Africa region.